2009
DOI: 10.1037/a0016999
|View full text |Cite
|
Sign up to set email alerts
|

Patient and therapist perspectives on session depth in relation to technique during psychodynamic psychotherapy.

Abstract: This study investigates the relationship between therapist techniques with patient and therapist ratings of session Depth (powerful, valuable, deep, full, and special). Eighty-three patients were admitted to a university-based community outpatient psychological clinic, and videotapes of an early treatment session were reliably rated by trained coders to identify techniques used by therapists. Overall amount of psychodynamic-interpersonal technique was found to have a significant positive correlation with patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…All participants taking part in this study said they enjoyed talking to their therapist about their difficulties and felt they were able to engage well with therapy sessions. In common with findings from the general adult mental health population (Pesale & Hilsenroth 2009), many participants said they found talking beneficial in itself, and appreciated that their therapists spoke to them in an in-depth fashion about their difficulties. Participants found therapy validating, saying that they felt they were listened to and that their problems were acknowledged and taken seriously.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…All participants taking part in this study said they enjoyed talking to their therapist about their difficulties and felt they were able to engage well with therapy sessions. In common with findings from the general adult mental health population (Pesale & Hilsenroth 2009), many participants said they found talking beneficial in itself, and appreciated that their therapists spoke to them in an in-depth fashion about their difficulties. Participants found therapy validating, saying that they felt they were listened to and that their problems were acknowledged and taken seriously.…”
Section: Discussionmentioning
confidence: 57%
“…The quality of client participation in therapy sessions has been linked to good outcomes (Orlinsky et al 1994). Both clients and therapists report that therapeutic discussions that have depth (Stiles 1980;Pesale & Hilsenroth 2009), and lead to new insights and awareness, are helpful (Elliot 1985;Mahrer & Nadler 1986;Martin & Stelmaczonek 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Linking these findings to other process variables from this sample, Pesale and Hilsenroth () found that the use of greater exploratory dynamic techniques in early sessions was important for helping patients experience these sessions as more powerful, valuable, deep, full and special. Similarly and more generally, Hoglend and Heyerdahl () found that patients' capacities to ‘manifest verbal fluency’ were positively related to outcome as well as improved occupational and relational functioning at the end of treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Addressing this component of the relationship as therapists did in our sample creates a potential for a corrective emotional experience that can be generalized to other relationships (for verbatim clinical examples see : Carsky, 2013;Diener & Pierson, 2013;Lingiardi, 2013;Slavin-Mulford, 2013;Stricker, 2013). Pesale and Hilsenroth (2009), again using an overlapping sample with the current data, found that greater use of psychodynamic exploratory techniques allows patients to experience their sessions with greater depth, as valuable and meaningful.…”
Section: Discussionmentioning
confidence: 82%